Sintesis Artemeter dengan Katalis Bifungsional dalam Satu Sistem Reaksi dan Uji Aktivitas Sitotoksik Terhadap Sel Leukimia L1210 - LIA NURLIANA; HARMITA HARMITA; SILVESTER S. TURSILOADI; L.B. S KARDONO (JURNAL ILMU KEFARMASIAN INDONESIA, 2012)
Artemisinin has been known as herbal medicine from China, which was isolated from the Artemisia annua L. plant. Artemisinin was originally known as antipyretic and antimalarial drug. Artemisinin and its derivatives also have potential as anticancer, due to the sesquiterpene lactone containing a unique peroxide group. This study aimed to modify the structure of artemisinin into artemether using solid catalyst Ni/TiO2-SO4 through the hydrogenation and methylation of the alcohol group in one pot reaction system. The product was then investigated for its cytotoxic activity against L1210 leukemia cells. The solid catalyst in this study was composed of metalic Ni as the active center, TiO2 as a catalyst support and sulphate as the promoter. The modification of artemisinin produced 1.29% artemether white crystalls as a minor product, and 19% dihidroartemisinin as an intermediate compound. The synthesized artemether showed an anticancer activity against L1210 leukimia cells with IC50 value of 3.07 µg / mL. The result suggests that the synthesized artemether has a potency as an anticancer.